Prospective data linkage to facilitate COVID-19 trials – A call to action. (2020) - PA, PA; Sydes, Sydes; MR, MR; McGrail, McGrail; KM, KM; Morris, Morris; AD, AD; Schull, Schull; MJ, MJ; Walker, Walker; R, R
No abstract available